Public Perceptions of Halal Tourism Infrastructure in Pekalongan, Central Java - Kuat Ismanto; Happy Sista Devy (Share: Jurnal Ekonomi dan Keuangan Islam, 2022)
Pekalongan City is known for its creative city and religious people, which can be a competitive advantage in developing halal tourism destinations. However, having that alone is insufficient; infrastructure readiness is also crucial. This paper seeks to describe public perceptions of Pekalongan City’s readiness to become a halal tourism destination in terms of its infrastructure. Primary data was collected through the random distribution of questionnaires. Using the accidental sampling method, a total of 65 people were selected as a sample. Data was also gathered through interviews with key informants, who were selected using a purposive random sampling method. The criterion is that the informants have visited tourist attractions in Pekalongan City. The secondary data was gathered through a review of books, journal articles, research reports, websites, and other sources pertinent to the research topic. This study reveals that the community has a favorable view of Pekalongan City’s tourism infrastructure in terms of attractions, access, environment, and amenities. From this perception, it is concluded that Pekalongan City deserves to be a halal tourism destination. Although a positive impression is made, there is still room for development in areas like worship facilities, public restrooms, tourist attractions’ safety and comfort, and more. This study recommends that the local government invest in infrastructure to improve tourism services. A successful regional halal tourism industry will produce a tourist-attractive halal industry. Thus, establishing a good halal tourism destination begins with ensuring the location has the necessary infrastructure in place.========================================================================================================ABSTRAK – Persepsi tentang Infrastruktur Pariwisata Halal di Pekalongan, Jawa Tengah. Kota Pekalongan dikenal dengan kota kreatif dan masyarakatnya yang agamis yang dapat menjadi keunggulan kompetitif dalam membangunan destinasi wisata halal. Akan tetapi, tidak cukup hanya itu, kesiapan infrastruktur juga menjadi bagian yang sangat penting. Tujuan tulisan ini adalah mengeksplorasi persepsi masyarakat tentang kesiapan Kota Pekalongan menjadi destinasi wisata halal, terutama infrastrukturnya. Data primer diperoleh melalui penyebaran kuesioner secara acak kepada 65 responden yang dipilih dengan teknik accidental sampling. Selain itu, data juga diperoleh melalui wawancara mendalam dengan narasumber yang ditentukan secara purposive sampling dengan kriteria pernah berkunjung ke objek wisata di Kota Pekalongan. Data sekunder diperoleh melalui telaah buku, artikel jurnal, laporan penelitian, website, dan sumber lainnya yang mendukung tema penelitian. Hasil kajian menunjukkan bahwa masyarakat memiliki persepsi yang baik terhadap infrastruktur pariwisata Kota Pekalongan, baik pada komponen atraksi, akses, lingkungan, maupun amenitas. Dari persepsi ini diperoleh deskripsi bahwa Kota Pekalongan layak menjadi destinasi pariwisata halal. Meskipun demikian, masih ada ruang perbaikan yang diperlukan, seperti kelayakan fasilitas ibadah, kebersihan toilet, keamanan dan kenyamanan destinasi wisata, dan sebagainya. Kajian ini merekomendasikan agar pemerintah daerah berinvestasi dalam infrastruktur untuk meningkatkan layanan pariwisata. Industri wisata halal daerah yang berhasil akan menghasilkan industri halal yang menarik bagi wisatawan. Oleh karena itu, pemilihan destinasi wisata halal yang baik harus dimulai dengan memastikan adanya infrastruktur yang memadai di lokasi dimaksud.